IN SILICO INVESTIGATION OF ECHINACEA PURPUREA PHYTO LIGANDS TARGETING HUMAN PAPILLOMAVIRUS TYPE 18’S L1 PROTEIN: IMPLICATIONS FOR CERVICAL CANCER MANAGEMENT - VINAYA VINOD SHINDE; SAKSHI CHAUDHARY; PARMINDER KAUR; SWATI BANKARIYA (Innovare Journal of Medical Sciences, 2024)
Objectives: Human papillomavirus (HPV) is a highly oncogenic virus responsible for the majority of intraepithelial lesions and cervical cancer. Among various HPV types, 16 and 18 contribute to approximately 70% of cervical cancer cases globally, making them the most prevalent high-risk oncogenic variants associated with this disease. Numerous vaccines (Gardasil 9, Gardasil, and Cervarix) have been approved by FDA to combat HPV infections; however, their widespread implementation faces challenges due to their limited cost-effectiveness. Methods: Echinacea purpurea’s components have already been studied for in silico analysis against HPV Type 16’s L1 protein. In the present analysis, we aimed to explore the potential interaction between E. purpurea phytoligands (curcumin, echinacoside, and chicoric acid) and the major capsid protein L1 of HPV type 18 (2R5I) through molecular docking analysis. Results: Molecular docking analysis revealed that the echinacoside, one of the components of E. purpurea, has the best binding affinity (−7.9 kcaL/moL) against the L1 protein of the HPV type 18. Conclusion: The molecular docking analysis indicates that E. purpurea could act as an inhibitor against HPV infection. Further research and in vivo studies are necessary to confirm its efficacy as a cost-effective alternative to present HPV vaccines.